Leadership of networks and performance : a qualitative and quantitative analysis - Ruckdäschel, Susanne (Markt- und Unternehmensentwicklung Markets and Organisations, 2015)
In contrast to hierarchical leadership within intra-organizational contexts, leaders of inter-organizational networks have to lead across organizational boundaries without hierarchical fiat or directive authority. The central research question of Susanne Ruckdäschel is how leadership behavior of network managers can influence network performance. Hereby, relational leadership in the form of empowering leadership is regarded as decisive criterion. Her study focuses on the interplay between network leaders and network companies. The perspectives of both the network managers and the network members are illuminated. Therefore, first, a mixed methods study is conducted from the perspective of the network managers and second, a quantitative analysis based on a structural equation model focuses on the perspective of the network members. Contents  Leadership of regional networks  Empowering leadership  Network performance  Cultural and structural differences Target Groups Lecturers and students of business administration with a focus on leadership, international management and/or regional development  Network or cluster managers, policy makers, and SMEs in regional networks The Author Susanne Ruckdäschel received her PhD at the University of Passau, where she was affiliated to the Chair of International Management (Prof. Dr. Carola Jungwirth). Her research interests include leadership of regional networks as well as intercultural comparisons of regional networks.